2016
DOI: 10.3346/jkms.2016.31.3.430
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-6 Receptor Polymorphisms Contribute to the Neurological Status of Korean Patients with Ischemic Stroke

Abstract: To investigate the contribution of the interleukin-6 receptor (IL-6R) gene single nucleotide polymorphisms (SNPs) to the neurological status of Korean patients with ischemic stroke (IS), two SNPs of the IL-6R gene (rs4845617, 5 UTR; rs2228144, Ala31Ala) were selected. IS patients were classified into clinical phenotypes according to two well-defined scores: the National Institutes of Health Stroke Survey (NIHSS) and the Modified Barthel Index scores. There were 121 IS patients and 291 control subjects. The SNP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 36 publications
0
4
1
Order By: Relevance
“…Interleukin-6 (IL-6) as a cytokine plays an important role in the "response to injury" model of endothelial cells and atherosclerosis (26), and it is encoded and regulated by the IL-6 receptor (IL6R) gene, which is located in the chromosome 1q21. Some studies revealed that polymorphisms of IL-6R increased the risk of ischemic stroke in patients with metabolic syndrome and were associated with the neurologic status of ischemic stroke patients (27,28). However, we did not find the associations between the other 18 SNPs and outcomes in our linkage analysis.…”
Section: Discussioncontrasting
confidence: 80%
“…Interleukin-6 (IL-6) as a cytokine plays an important role in the "response to injury" model of endothelial cells and atherosclerosis (26), and it is encoded and regulated by the IL-6 receptor (IL6R) gene, which is located in the chromosome 1q21. Some studies revealed that polymorphisms of IL-6R increased the risk of ischemic stroke in patients with metabolic syndrome and were associated with the neurologic status of ischemic stroke patients (27,28). However, we did not find the associations between the other 18 SNPs and outcomes in our linkage analysis.…”
Section: Discussioncontrasting
confidence: 80%
“…The present study found that Klotho overexpression induced by LV-KL directly inhibited RIG-I expression in the ischemic brain. Additionally, a recent study showed that Klotho gene overexpression significantly decreased IL-6 production in HUVECs with or without inflammatory challenge ( Xia et al, 2016 ), and IL-6 receptor polymorphisms contributed to neurological status in ischemic stroke patients ( Kim et al, 2016 ). The binding of IL-6 to the IL-6 receptor activates intracellular signaling cascades and the production of C-reactive protein (CRP) and other cytokines ( Wang et al, 2010 ).…”
Section: Discussionmentioning
confidence: 99%
“…IL-6 has been detected in plasma and cerebrospinal fluid of stroke patients, and IL-6 immunoreactivity has been detected in microglia and cortical neurons of ischemic stroke models ( 96 ). In patients, IL-6R polymorphisms are also related to poor neurological outcomes ( 97 ), although IL-6 polymorphisms did not show an increased risk of ischemic stroke ( 98 ). To add to the conflicting observations, IL-6-deficient mice and mice treated with an IL-6 receptor antagonist mice did not have improved outcomes compared to untreated mice ( 99 , 100 ).…”
Section: Inflammation In Strokementioning
confidence: 99%